Building trust in the fabric of sustainability ratings: An impression management perspective. (1st July 2020) - Boiral, Olivier; Brotherton, Marie-Christine; Talbot, David
Abstract: The objective of this paper is to analyze the impression management strategies that practitioners in the sustainability rating industry use to build confidence in the reliability of ratings and explain these ratings' lack of convergence. Based on semi-structured interviews with 36 practitioners, this study sheds more light on the socially constructed nature of sustainability ratings and the rhetoric used to defend the reliability and materiality of measurements. This rhetoric revolves around seven impression management strategies. These include four assertive strategies that highlight the distinctive competences, commercial capabilities, access to privileged information, and methodology used, and three defensive strategies that rely on lack of standardization in sustainability measurements, difficulties in finding reliable data, and elastic interpretations of materiality. This study offers contributions to the critical literature on sustainability rating agencies, performance measurement, and impression management strategies. Managerial implications and avenues for future research are also described.